تأثير الملوحة على نمو وإنتاج بعض أصناف الكينوا - فطحيزة سعد, ايمان; فطحيزة سعد, شيماء; فطحيزة سعد, صفاء (University of Eloued جامعة الوادي, 2023)
This study was conducted on three varieties of quinoa (black V1, red V2, yellow V3), which were treated with different concentrations of salinity by spraying (0-100-200-400-600) m mol/L in order to know the effect of salinity (Nacl) on the growth of The germination of the quinoa plant by measuring the parameters: The area of the paper ,Dry and wet weight,The percentage of cellular fullness( The photosynthetic pigments chlorophyll (a + b) and carotenes(. The obtained results confirmed the ability of the studied cultivars to tolerate salinity in varying degrees, as V1 showed the highest tolerance to high salinity levels, followed by V2 in a medium manner, while V3 was the least tolerant of them.
التنوع الحيوي وفيزيولوجيا النبات
Keywords: الكينو; quinoa - germination - growth - salt stress - tolerance